Early intervention and identification of gambling disorder: a systematic literature review of strategies implemented by gambling operators - Škařupová, Kateřina; Vlach, Tomáš; Mravčík, Viktor (Central European Journal of Public Health, 2020)
OBJECTIVE: Recent developments in online lotteries and betting and in digitalization of land-based gambling devices bring new opportunities to track behaviour of individual players and to identify and address developing problem in its initial stages. Early identification of gambling disorder allows for timely intervention and increases the likelihood of successful recovery and minimises harms. Our review aims to examine what on-site strategies are available in both online and offline gambling venues to early identify and address the developing gambling problem while also assessing their effectiveness and strength of the evidence. METHODS: We searched main academic databases and other internet resources and collected 67 peer-reviewed papers and grey literature documents that describe one or more such strategies. RESULTS: Available measures ranged from information provision, gambling behaviour surveillance and associated personalized interventions to setting limits and self-exclusion. CONCLUSIONS: Although a number of methods how to address disordered gambling are available to gambling operators, there is still insufficient evidence about the validity and reliability of identification strategies and about effectiveness of the intervention methods.
Keywords: Early Medical Intervention; časná lékařská intervence; Early Diagnosis; hráčství; lidé; Humans; Gambling; časná diagnóza